Evaluation of commercial Syzygium aromaticum L. (clove) essential oil samples from market in accordance with the European Pharmacopoeia 10.0 criteria - Barak, Timur Hakan; Gultekin, Ediz; Senturk, Tugba Buse; Ozdemir, Kevser (Marmara Univ, 2024)
Clove (Syzygium aromaticum L.) oil is widely used in cosmetics, medicine and food industries. Previous studies have revealed many pharmacological effects of clove oil, including anti-infective, antioxidant, anesthetic and anti-inflammatory. In this study, clove essential oil (CEO) samples obtained from different places in T & uuml;rkiye, have been extensively evaluated in terms of their compliance with European Pharmacopoeia (EP) standards, which is the official guide that includes international rules and methods. In this study, 13 CEO obtained from Turkish market (Pharmacy and other) were analyzed according to the criteria specified in the Clove Oil monograph in European Pharmacopoeia 10.0. Appearance, solubility, thin layer chromatography, relative density, refractive index, optical rotation analysis was conducted for all samples. In addition, GC-MS was used to elucidate detailed phytochemical profiles of the samples. Results revealed that none of the samples from Turkish Market fully met the EP criteria. When the difference between the sources of purchase evaluated, results revealed that there is a significant difference between the sources from which the oils are taken in terms of standards. The deficiency of the CEO samples to fulfil standards of the EP indicates the requirements of performing the necessary effort and auditing to increase the quality of the products on the market.
Keywords: Clove oil; European pharmacopoeia; GC-MS; essential oil; Syzygium aromaticum L